Notas sobre el comportamiento y la migración de Urania fulgens (Lepidoptera: Uraniidae) en Costa Rica - Murillo-Hiller, Luis Ricardo (Instituto de Ecología, A.C., 2008)
Observations on U. fulgens behavior were done in Costa Rica during a mass migration in 2005; notes on the behavior of a non-migratory population are also documented. Tapantí National Park seems to be a possible destiny for the migrating butterflies. A new possible larval food plant is recorded.